The molecular genetics of erythropoietic protoporphyria - Elder, G H; Gouya, L; Whatley, S D; Puy, H; Badminton, M N; Deybach, J C (Cellular and Molecular Biology, 2009)
Erythropoietic protoporphyria (EPP) is a syndrome in which accumulation of protoporphyrin IX in erythroid cells, plasma, skin and liver leads to acute photosensitivity and, in about 2% of patients, liver disease. More than 95% of unrelated patients have ferrochelatase (FECH) deficiency (MIM 177000) while about 2% have X-linked dominant protoporphyria (XLDPP) (MIM 300752) caused by gain-of-function mutations in the ALAS2 gene. Most FECH-deficient patients are compound heterozygotes for a hypomorphic allele (FECH IVS3-48C) and a deleterious FECH mutation that together lower FECH activity to around 30% of normal. The frequency of the IVS3-48C allele varies between populations, ranging from less than 1% to 45%. About 4% of unrelated FECH-deficient patients are compound heterozygotes or homozygotes for rare FECH mutations and have lower enzyme activities. Acquired somatic mutation of FECH secondary to myeloid disease may rarely cause EPP. The risk of liver disease is increased in XLDPP and in FECH-deficient patients who are hetero- or homoallelic for rare FECH mutations. Inherited FECH-deficient EPP is an autosomal recessive disorder with some families showing pseudodominant inheritance; the proportion of such families being determined by the population frequency of the IVS3-48C allele.